2015
DOI: 10.1097/rlu.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoscintigraphy for the Assessment of Autologous Stem Cell Implantation in Chronic Lymphedema

Abstract: Lymphoscintigraphy is the criterion standard technique for the diagnosis of lymphedema. The authors present the images acquired before and 6 months after implantation of autologous stem cells in 2 patients with chronic lymphedema of the lower limbs. The stem cells implantations were carried out by multiple superficial and deep injections in the trajectory of the lymphatic vessels and also in the inguinal region. A volume of 0.75 to 1.00 mL of cell suspension (1.0-2.2 × 10(9) stem cells) was administered in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…They exert antiwrinkle effects by reducing ultraviolet-B-induced apoptosis, stimulating collagen synthesis of dermal fibrosis [26], and modifying the local microenvironment [27]. Three studies that used ADSC transplantation for the therapy of human lymphedema had been reported [28][29][30]. In these clinical studies, a greater number of lymph nodes and an improvement in the patient-reported outcomes were confirmed after therapies.…”
Section: Introductionmentioning
confidence: 99%
“…They exert antiwrinkle effects by reducing ultraviolet-B-induced apoptosis, stimulating collagen synthesis of dermal fibrosis [26], and modifying the local microenvironment [27]. Three studies that used ADSC transplantation for the therapy of human lymphedema had been reported [28][29][30]. In these clinical studies, a greater number of lymph nodes and an improvement in the patient-reported outcomes were confirmed after therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Peña Quián et al[ 46 ] provided a case report on a patient with edematous lower limbs resulting from recurrent lymphangitis. Autologous ADSCs (1-2.2 × 10 9 ) were injected and a greater number of new lymphatic ramifications and lymph nodes were observed at 6 mo post-treatment via lymphoscintigraphy.…”
Section: Adsc-based Therapiesmentioning
confidence: 99%
“…Lymphatic system imaging in nuclear medicine directly reflects the function of lymphatic drainage [9–16] . For many years, lymphoscintigraphy has been widely considered as the first-line imaging to confirm the diagnosis of lymphedema and to visualize the functional state of the lymphatic system [15,17–23] …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] For many years, lymphoscintigraphy has been widely considered as the first-line imaging to confirm the diagnosis of lymphedema and to visualize the functional state of the lymphatic system. [15,[17][18][19][20][21][22][23] The purpose of this study was to investigate the relationship between iliolumbar LNs, inguinal LNs, and unilateral pelvic cancer-related lymphedema by retrospective analysis of 99m Tcantimony sulfide colloid (ASC) lymphoscintigraphy data.…”
Section: Introductionmentioning
confidence: 99%